2014
DOI: 10.1371/journal.pone.0113280
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interaction between Plant-Beneficial Rhizobacteria and Roots: Colonization Induces Corn Resistance against the Root Herbivore Diabrotica speciosa

Abstract: A number of soil-borne microorganisms, such as mycorrhizal fungi and rhizobacteria, establish mutualistic interactions with plants, which can indirectly affect other organisms. Knowledge of the plant-mediated effects of mutualistic microorganisms is limited to aboveground insects, whereas there is little understanding of what role beneficial soil bacteria may play in plant defense against root herbivory. Here, we establish that colonization by the beneficial rhizobacterium Azospirillum brasilense affects the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…Presumably, transformed maize line 201-L1 and its isogenic line HiII vary solely on the emission of EbC and each produced similar amounts of other secondary metabolites and CO 2 (Degenhardt et al 2009). Second instars WCR were previously shown to select host plants with a suitable density of conspecific larvae using the induced EbC in a dosedependent manner (Robert et al 2012b), whereas D. speciosa Santos larvae did not respond to this plant volatile (Santos et al 2014). Second instar larvae apparently not only used EbC but also ethylene as a signal to locate suitable host plants (Robert et al 2012a).…”
Section: Discussionmentioning
confidence: 98%
“…Presumably, transformed maize line 201-L1 and its isogenic line HiII vary solely on the emission of EbC and each produced similar amounts of other secondary metabolites and CO 2 (Degenhardt et al 2009). Second instars WCR were previously shown to select host plants with a suitable density of conspecific larvae using the induced EbC in a dosedependent manner (Robert et al 2012b), whereas D. speciosa Santos larvae did not respond to this plant volatile (Santos et al 2014). Second instar larvae apparently not only used EbC but also ethylene as a signal to locate suitable host plants (Robert et al 2012a).…”
Section: Discussionmentioning
confidence: 98%
“…This observation could be a boon for strategies using induced plant defenses to augment biological control in conjunction with other strategies to repel D. speciosa larvae27. Because larvae do not preferentially respond to elicitor treated plants, induced plant defense will likely not attract belowground larval pest populations in the field while augmenting control through recruitment of entomopathogenic nematode natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some speculation that root hairs may offer some protection by preventing very small herbivores (e.g., neonates) from reaching and penetrating the root epidermis or may possibly provide refugia for natural enemies of herbivores such as entomopathogenic nematodes (Johnson et al, 2016a). Although not strictly a physical defense, root hairs may also increase the root surface available for colonization by beneficial soil microbes, which in turn can sometimes confer resistance to insect and nematode herbivores of grasses (Piskiewicz et al, 2009; Santos et al, 2014). Notably, root hairs can be induced, for example by plant-parasitic nematodes in barley (Haase et al, 2007).…”
Section: Get Tough—physical Defensesmentioning
confidence: 99%
“…The plant parasitic nematode Tylenchorhynchus ventralis is strongly controlled by soil microbes in a coastal foredune grassland (Piskiewicz et al, 2009) and colonization of maize by the rhizobacterium Azospirillum brasilense can deter, and reduce the performance of, western corn rootworm (Santos et al, 2014). However, another study of three plant species, including the grass Holcus lanatus , found no effect of the soil microbial community on defense against nematodes (Wurst et al, 2009).…”
Section: Get a Bodyguard—recruitment Of Natural Enemiesmentioning
confidence: 99%